Exploring the effect of industrial structure adjustment on interprovincial green development efficiency in China: A novel integrated approach. (November 2019) - Zhu, Bangzhu; Zhang, Mengfan; Zhou, Yanhua; Wang, Ping; Sheng, Jichuan; He, Kaijian; Wei, Yi-Ming; Xie, Rui
Abstract: Industrial structure adjustment is one of the effective measures for achieving green development. Aiming at improving green development efficiency through industrial structure adjustment, this study proposes a novel integrated approach incorporating industrial structure adjustment measurement, super-efficiency slacks-based measure with undesirable outputs and panel regression models to explore the effect of industrial structure adjustment on green development efficiency. Taking the provincial data of China from 1999 to 2016 as an example, the empirical results show that during the study period, China's provincial industrial structure rationalizations and advancements have three trends, i.e. rising, U-shaped and inverted U-shaped. In the meantime, China's provincial green development efficiency also has three trends, i.e. rising, falling and U-shaped. Industrial structure rationalization and advancement both have a positive effect on green development efficiency. Compared with the industrial structure rationalization, the advancement has a greater effect on green development efficiency. Environmental protection, urbanization, energy conservation and emission reduction policy are conducive to improving green development efficiency. However, human capital and openness have a negative effect on green development efficiency. Highlights: An integrated approach is proposed to explore the effects of carbon trading mechanism on green development efficiency. Industrial structure rationalization and advancement are used firstly to measure the levels of industrial structure adjustment. Super-efficiency SBM model with undesirable outputs is used to measure green development efficiency. The empirical results show that industrial structure adjustment can improve green development efficiency.